The Role of Corporate Governance on the Efficiency of Banks Considering the Mediating Role of Financial Health - Yasna Ghaderi; Hamzeh Didar; Mehdi Heydari (Iranian Journal of Accounting, Auditing & Finance)
This study aimed to examine the financial health of the corporate governance-bank efficiency relationship. The statistical population encompasses all commercial, non-commercial, and specialised banks during 2011-2019. Since its statistical value is low, the sample size equals the statistical population. According to previous studies and various sources, the efficiency of banks was calculated using a nonparametric data envelopment analysis (DEA) method. Corporate governance was computed using the associated dummy variables. The index of financial health determinants was also estimated using the CAMELS system and ranked by Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) method. Findings showed that corporate governance has a significant effect on the efficiency of banks and the financial health of banks. In addition, financial health has a significant effect on the efficiency of banks. Since the study's first hypothesis was not rejected, financial health with an incomplete mediating role significantly affected the relationship between corporate governance and bank efficiency.